2022
DOI: 10.3390/biology11111570
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Profiling in Aging Studies

Abstract: Organism aging is closely related to systemic metabolic changes. However, due to the multilevel and network nature of metabolic pathways, it is difficult to understand these connections. Today, scientists are trying to solve this problem using one of the main approaches of metabolomics—untargeted metabolome profiling. The purpose of this publication is to review metabolomic studies based on such profiling, both in animal models and in humans. This review describes metabolites that vary significantly across age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 127 publications
(185 reference statements)
1
3
0
Order By: Relevance
“…Regarding lipid metabolites, studies have reported that specific metabolites are associated with increasing age (for review, see [ 1 , 14 , 15 ]), and our findings are in line with some of the previous studies. For instance, some lipid metabolites involved in lipid metabolism (such as fatty acids, carnitine, cholesterol, beta-hydroxybutyrate) and benzoate metabolism (such as hippuric acid), as well as citrulline and C-glycosyl tryptophan, have been shown to increase with age [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding lipid metabolites, studies have reported that specific metabolites are associated with increasing age (for review, see [ 1 , 14 , 15 ]), and our findings are in line with some of the previous studies. For instance, some lipid metabolites involved in lipid metabolism (such as fatty acids, carnitine, cholesterol, beta-hydroxybutyrate) and benzoate metabolism (such as hippuric acid), as well as citrulline and C-glycosyl tryptophan, have been shown to increase with age [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Because of its close connection to phenotypes, metabolomics has been used in studies aimed at deciphering biological mechanisms that drive changes in metabolism with aging. For example, previous studies found that metabolites such as lipids, carbohydrates, carnitines, and amino acids vary substantially by age [ 1 ]. However, the previous studies had important limitations, including the fact that they included individuals that were not screened to be healthy.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous metabolomics investigations have revealed substantial variations in metabolite profiles across different age cohorts, spanning diverse categories such as amino acids, carbohydrates, biogenic amines, and lipids. Additionally, these studies have elucidated aging-related metabolic pathways, including amino acid metabolism, lipids, and energy metabolism [ 7 ]. Given the absence of prior nuclear magnetic resonance (NMR)-based metabolomics investigations concerning the treatment of rat aging models using hemp seed oil, we conducted an exploratory study to address this research gap.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic differences can also influence the body's metabolism, leading to individual metabolomic profile differences. In addition, metabolomic profiles can change during different stages of life, such as during growth, aging, or in response to hormonal changes[ 6 ]. Analyzing these changes through metabolomics can provide valuable insights into the biochemical pathways affected by various conditions, potentially aiding in disease diagnosis, understanding biological mechanisms, and developing targeted treatments or interventions[ 7 ].…”
Section: Introductionmentioning
confidence: 99%